Geronimo - Thompson, William 1931-; Thompson, Dorcas (Philadelphia : Chelsea House Publishers, 2002)
Examines the life of the Apache chief Geronimo, who led one of the last Indian uprisings.
Includes bibliographical references (p. 62) and index.
Keywords: Geronimo (1829-1909) -- 1829-1909; Apache Indians -- Biography; Apache Indians -- Wars; Native Americans -- Biography -- New Mexico